2005
DOI: 10.1095/biolreprod.104.034967
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of the Genes Involved in Maturation and Development of the Rainbow Trout Ovary1

Abstract: Development and maturation of the ovary requires precisely coordinated expression of specific gene classes to produce viable oocytes. We undertook identification of some of the genes involved in these processes by creating ovary-specific cDNA libraries by suppression subtractive hybridization and by microarray-based analyses. We present 5778 tissue- and sex-specific genes from subtracted ovary and testis libraries, many of which remain unidentified. A microarray containing 3557 salmonid cDNAs was used to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 42 publications
5
53
1
Order By: Relevance
“…As stated above, the most striking result of this study was the much higher number of chromosomal regions influencing transcript abundance in the female compared to the male data set of identical sample size. Although several studies recently reported sex-specific transcript regulation (Von Schalburg et al 2005;McIntyre et al 2006), including for muscle tissue (Yang et al 2006), this possibility is challenged here by the alternative hypothesis that the sex-specific architecture we observed reflects adaptive sex-linked effects. In addition, other hypotheses concerning the genetic architecture of whitefish and the experimental cross itself have to be explored.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…As stated above, the most striking result of this study was the much higher number of chromosomal regions influencing transcript abundance in the female compared to the male data set of identical sample size. Although several studies recently reported sex-specific transcript regulation (Von Schalburg et al 2005;McIntyre et al 2006), including for muscle tissue (Yang et al 2006), this possibility is challenged here by the alternative hypothesis that the sex-specific architecture we observed reflects adaptive sex-linked effects. In addition, other hypotheses concerning the genetic architecture of whitefish and the experimental cross itself have to be explored.…”
Section: Discussionmentioning
confidence: 59%
“…Indirect labeling was performed on individual cDNA following the Array 50 kit protocol (Genisphere). Transcriptome profiles were obtained by using the 16,006-cDNA gene microarray (version 2) developed for Atlantic salmon (Salmo salar) by cGRASP (Von Schalburg et al 2005) (Consortium for Genomic Research on All Salmonids Project) and successfully tested and applied to other salmonid species, including Coregonus clupeaformis Rise et al 2007). Gene identification with the corresponding EST sequence can be found at http:/ /web.uvic.ca/ cbr/grasp/.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first salmonid 16K cDNA microaarray appeared in 2004. This array was developed by the Genomic Research on Atlantic Salmon Project (GRASP) (von Schalburg et al, 2005a) and led to the most recent 32K cDNA and the first 5K oligo DNA of 70-mer microarrays. The high sequence similarity (~ 86 %) between salmonids (9 genera and 68 species) indicates that cDNA microarrays may be suitable for studies involving any member of this fish family.…”
Section: Microarrays In the Study Of The Salmonid/ihnv/vhsv Modelsmentioning
confidence: 99%